Health and long-term care insurance wealth in Austria - Reinhard Koman; Maria M. Hofmarcher; Robert Holzmann (Oesterreichische Nationalbank (OeNB), 2025)
Estimates of social insurance pension wealth are available for a number of Western economies, including Austria for the year 2017. Such wealth may be compared with conventional wealth in terms of size and distribution and when we add such estimates to measures of wealth in the conventional sense, we arrive at measures of augmented wealth. In this paper, we estimate health and long-term care insurance wealth in Austria and add that to conventional wealth estimates for Austria to achieve a further measure of augmented wealth. To our knowledge, this is the first attempt worldwide to do this. The resulting magnitude of health and long-term care insurance wealth is substantial, namely EUR 238,000 at the household level. It is comparable in scale to both pension insurance wealth (EUR 245,000) and net wealth in the conventional sense, i.e. property plus financial wealth minus debt (EUR 250,000). As regards distributive characteristics, health and longterm care insurance wealth is rather equally distributed (Gini coefficient of 0.31), compared to pension insurance wealth (0.45) and conventional wealth in Austria (0.73). The Gini coefficient for the new augmented wealth distribution (conventional wealth plus health and long-term care insurance wealth) is 0.47.
Keywords: D31; H51; I13; 330; net wealth; health insurance; long-term care; augmented wealth; HFCS